ESTABLISHING CAUSE-AND-EFFECT RELATIONSHIPS BETWEEN THE INTEGRAL INDICATOR OF THE LEVEL OF PROVISION OF GEOSPATIAL DEVELOPMENT OF TERRITORIAL COMMUNITIES AND THE GENERALIZING FACTOR OF REGIONAL DEVELOPMENT - Нестеренко, Сергій; Гой, Василь; Халіков, Сергій; Вяткін, Роман (SWorldJournal, 2024)
The relevance of the research topic is proven. It is proposed to consider geospatial development as a systemic category that is influenced by functional, spatial, urban planning, regulatory, security, stakeholder, environmental, infrastructural, investme